Analisis Pengaruh Harga, Promosi, dan Kualitas Produk Terhadap Keputusan Pembelian pada UMKM Kuliner Menggunakan SPSS - Hamzah Ramadhan; A.M. Al Maghrobi; Salman Alfarisi; Rivaldy Andreal Linium; Bettran Ayik Prasetyo (PT Cendekia Education Center, 2026)
This study aimed to examine the influence of price, promotion, and product quality on purchasing decisions in culinary micro, small, and medium enterprises (MSMEs) using a quantitative approach with multiple linear regression analysis. The study was conducted on 25 culinary MSMEs in Probolinggo City selected through saturated sampling. Data were collected using a questionnaire measuring the variables of price (X₁), promotion (X₂), product quality (X₃), and purchasing decision (Y). Data were analyzed using multiple linear regression and Analysis of Variance (ANOVA) with the assistance of SPSS software to determine the simultaneous effect of the independent variables on purchasing decisions. The findings revealed that price, promotion, and product quality simultaneously had a significant effect on purchasing decisions, with a significance value of 0.005 (< 0.05). These results indicate that the combination of the three variables plays an important role in influencing consumer purchasing decisions in culinary MSMEs in Probolinggo City. Therefore, culinary MSME owners are encouraged to optimize pricing strategies, promotional activities, and product quality simultaneously to enhance consumers' purchasing decisions.